1993
DOI: 10.1111/j.1365-2249.1993.tb06495.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological responses of Gambians in relation to clinical stage of HIV-2 disease

Abstract: SUMMARYThis study describes a broad spectrum of cellular and antibody-mediated immune responses found in 28 asymptomatic and 37 symptomatic Gambian patients with HIV-2 infection. It shows that these responses vary according to the stage of infection as described by three clinical staging systems. The first system was a local one based on the signs used for the WHO Bangui clinical definition of AIDS, the second, suggested by WHO, was based on a performance scale, and the third was that used by the Centre for Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…This could potentially be delineated by incorporating a demographically similar BCG "naïve" population (such as individuals in the United States), but this introduces social and geographical (environmental mycobacteria) variables that makes them less than ideal comparators. The use of TST for the diagnosis of active disease in HIV-infected individuals has been controversial with previous studies reporting reduced sensitivity in this population (Goldstein et al 1994;Graham et al 1992;Johnson et al 1992;Lifson et al 1993;Mamani et al 2013;Whittle et al 1993). It is therefore noteworthy that we also found that the DPPD appeared to be more sensitive for the detection of active TB in HIV-infected individuals than PPD.…”
Section: Performance Of Skin Testing Relative To Cd4 T Cell Status Incontrasting
confidence: 50%
See 1 more Smart Citation
“…This could potentially be delineated by incorporating a demographically similar BCG "naïve" population (such as individuals in the United States), but this introduces social and geographical (environmental mycobacteria) variables that makes them less than ideal comparators. The use of TST for the diagnosis of active disease in HIV-infected individuals has been controversial with previous studies reporting reduced sensitivity in this population (Goldstein et al 1994;Graham et al 1992;Johnson et al 1992;Lifson et al 1993;Mamani et al 2013;Whittle et al 1993). It is therefore noteworthy that we also found that the DPPD appeared to be more sensitive for the detection of active TB in HIV-infected individuals than PPD.…”
Section: Performance Of Skin Testing Relative To Cd4 T Cell Status Incontrasting
confidence: 50%
“…The use of TST for the diagnosis of active disease in HIV-infected individuals has been controversial with previous studies reporting reduced sensitivity in this population (Goldstein et al 1994 ; Graham et al 1992 ; Johnson et al 1992 ; Lifson et al 1993 ; Mamani et al 2013 ; Whittle et al 1993 ). It is therefore noteworthy that we also found that the DPPD appeared to be more sensitive for the detection of active TB in HIV-infected individuals than PPD.…”
Section: Discussionmentioning
confidence: 99%
“…Among groups for whom immunological-based TB testing results are traditionally poor, Mtb infection is especially problematic in immune-compromised individuals that have an increased likelihood of progression to disease such that TB is a leading cause of death in HIV/AIDS patients. The use of TST for the diagnosis of active disease in HIV-infected individuals has been controversial with previous studies reporting reduced sensitivity in this population (Goldstein et al 1994 ; Graham et al 1992 ; Johnson et al 1992 ; Lifson et al 1993 ; Mamani et al 2013 ; Whittle et al 1993 ).…”
Section: Skin Tests In Immune-compromised Subjectsmentioning
confidence: 99%
“…The DTH reaction is mediated by T-helper cells that produce IL-2 and Although some correlation between DTH reactivity and T-cell count has been observed in HIVinfected individuals, DTH anergy has been reported to be an independent predictor of HIV-1 progression (80)(81)(82). Studies in Africa of HIV-1-and HIV-2-infected individuals have also shown a correlation between DTH reactivity and clinical stage of infection (83)(84)(85)(86). However, the rate of development of cutaneous anergy is slower in HIV-2 infection than it is in HIV-1 infection (14).…”
Section: T-lymphocyte Functionmentioning
confidence: 99%